Application of CoNi / C composite material in chlorofluoroalkane dehydrochlorination reaction

By using CoNi/C composite materials as catalysts, the problems of carbon accumulation and sintering of traditional catalysts in the dehydrogenation of HCBC and Alkanes were solved, the reaction yield and catalyst life were improved, and the catalytic effect with high efficiency and long life was achieved.

CN119633825APending Publication Date: 2025-03-18RUYUAN DONGYANG LIGHT FLUORIDE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581147.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing catalysts have carbon deposits and easy sintering in the dehydrogenation reaction of HFCA, resulting in the deactivation of the catalyst. The yield of HFO-1234yf is low and the composition is complex.

Method used

CoNi/C composite materials are used as catalysts to prepare by contacting cobalt, nickel and carbon sources, using the strong interaction of CoNi alloy and the limiting effect of the carbon matrix to avoid sintering and carbon accumulation and improve catalytic activity.

Benefits of technology

It improves the yield of the HCBC dehydrogenation reaction, extends the life of the catalyst, solves the problems of easy carbon accumulation and sintering of traditional catalysts, and is simple to operate and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633825A_ABST
    Figure CN119633825A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical catalysts, and provides an application of a CoNi / C composite material in a chlorofluoroalkane dehydrochlorination reaction, and a preparation method of the CoNi / C composite material comprises the step of contacting a cobalt source, a nickel source and a carbon source to obtain the CoNi / C composite material. The CoNi / C composite material can be used as a catalyst for a dehydrochlorination reaction of chlorofluoroalkanes, so that the problem that the catalyst is inactivated due to the phenomena of carbon deposition and easy sintering of the existing catalyst is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical catalysts, and in particular to application of a CoNi / C composite material in a dehydrochlorination reaction of fluorochloroalkanes. Background Art

[0002] At present, the main way to obtain HFO-1234yf (2,3,3,3-tetrafluoropropene) in industry is through the gas-phase catalytic dehydrogenation of HCFC-244bb (2-chloro-1,1,1,2-tetrafluoropropane). Since this reaction is a structure-sensitive reaction, traditional Lewis acid catalysts have disadvantages such as low selectivity for HFO-1234yf, low catalyst specific surface area, and easy carbon deposition, resulting in complex crude product composition and low HFO-1234yf yield. Traditional Lewis acid catalysts are prone to sintering and carbon deposition. The former is because the traditional Lewis acid catalyst has a low melting point, the grain size changes significantly before and after the reaction process, and the grains are easy to grow in high-temperature reactions; the latter is that the active sites of the catalyst are covered by olefin polymers, resulting in a decrease in the life of the catalyst. Therefore, it is urgent to provide a catalyst to solve the above problems. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a CoNi / C composite material, which is used as a catalyst in the dehydrochlorination reaction of fluorochloroalkanes to improve the carbon deposition and sintering phenomenon existing in the existing catalysts, resulting in the problem of catalyst deactivation.

[0004] To this end, the present invention provides an application of a CoNi / C composite material in a dehydrochlorination reaction of chlorofluoroalkanes. The preparation method of the CoNi / C composite material comprises contacting a cobalt source, a nickel source and a carbon source to obtain the CoNi / C composite material.

[0005] Aiming at the problem of carbon deposition and easy sintering in existing catalysts, which leads to the deactivation of catalysts, the present invention provides a CoNi / C composite material. Due to the strong interaction between metal atoms in CoNi alloy, the single-phase solid solution CoNi alloy makes the catalyst not easy to sinter and deactivate, and the confinement effect caused by the presence of the surrounding carbon matrix also hinders the sintering of CoNi alloy. And because the acid sites of Lewis acid of CoNi alloy are weak, it can accurately anchor the fracture of C-Cl bond, thereby improving the yield of fluorochloroalkane dehydrochlorination reaction, and greatly prolonging the life of catalyst. In addition, CoNi / C composite material has short preparation cycle, high yield of catalytic reaction, long life and simple operation, and belongs to environmentally friendly catalyst at the same time, which can be applied to industrial production.

[0006] According to an embodiment of the present invention, the cobalt source includes at least one of Co(C2H3O2)2, Co(NO3)2, and CoCl2.

[0007] According to an embodiment of the present invention, the nickel source includes at least one of Ni(C2H3O2)2, Ni(NO3)2, and NiCl2.

[0008] According to an embodiment of the present invention, the carbon source includes at least one of trimesic acid, citric acid, polyvinyl pyrrolidone, glycine, and urea.

[0009] According to an embodiment of the present invention, the preparation method of the CoNi / C composite material comprises:

[0010] Dissolving a cobalt source, a nickel source, a carbon source and an alkaline compound in a first solvent to obtain a first precursor of a CoNi / C composite material;

[0011] The first precursor of the CoNi / C composite material is subjected to a first calcination to obtain the CoNi / C composite material.

[0012] According to an embodiment of the present invention, the cobalt source includes CoCl2, the nickel source includes NiCl2, and the carbon source includes trimesic acid.

[0013] According to an embodiment of the present invention, the alkaline compound includes NaOH.

[0014] According to an embodiment of the present invention, the first solvent includes N,N-dimethylformamide.

[0015] According to an embodiment of the present invention, the first calcination temperature is 400-800°C, preferably 500-600°C.

[0016] According to an embodiment of the present invention, the first calcination time is 1 to 6 hours, preferably 2 to 4 hours.

[0017] According to an embodiment of the present invention, the first calcination atmosphere is an inert atmosphere, preferably nitrogen.

[0018] According to an embodiment of the present invention, the preparation method of the CoNi / C composite material comprises:

[0019] The cobalt source, the nickel source and the carbon source are mixed to obtain a second precursor of the CoNi / C composite material;

[0020] The CoNi / C composite material second precursor is subjected to a second calcination to obtain the CoNi / C composite material.

[0021] According to an embodiment of the present invention, the cobalt source includes Co(NO3)2, the nickel source includes Ni(NO3)2, and the carbon source includes citric acid.

[0022] According to an embodiment of the present invention, the second calcination temperature is 300-600°C.

[0023] According to an embodiment of the present invention, the second calcination time is 3 to 6 hours.

[0024] According to an embodiment of the present invention, the second calcination atmosphere is H2 / N2, and the volume ratio of H2 to N2 is (1:1) to (1:5), preferably (1:2) to (1:4).

[0025] According to an embodiment of the present invention, the preparation method of the CoNi / C composite material comprises:

[0026] The cobalt source, the nickel source and the carbon source are dissolved in a second solvent, and the CoNi / C composite material is obtained by hydrothermal treatment.

[0027] According to an embodiment of the present invention, the cobalt source includes Co(C2H3O2)2, the nickel source includes Ni(C2H3O2)2, and the carbon source includes polyvinyl pyrrolidone.

[0028] According to an embodiment of the present invention, the second solvent includes hydrazine hydrate.

[0029] According to an embodiment of the present invention, the temperature of the hydrothermal treatment is 90-160°C.

[0030] According to an embodiment of the present invention, the hydrothermal treatment time is 8 to 24 hours, preferably 14 to 20 hours.

[0031] According to an embodiment of the present invention, the fluorochloroalkane includes 2-chloro-1,1,1,2-tetrafluoropropane.

[0032] According to an embodiment of the present invention, the temperature of the fluorochloroalkane dehydrochlorination reaction is 400-600°C, preferably 450-550°C.

[0033] According to an embodiment of the present invention, the pressure of the fluorochloroalkane dehydrochlorination reaction is 0.1013-1 MPa, preferably 0.5-0.7 MPa.

[0034] According to an embodiment of the present invention, the dehydrochlorination reaction of fluorochloroalkane comprises reacting 2-chloro-1,1,1,2-tetrafluoropropane with hydrogen to obtain 2,3,3,3-tetrafluoropropene.

[0035] According to an embodiment of the present invention, the molar ratio of hydrogen to 2-chloro-1,1,1,2-tetrafluoropropane is (6:1) to (1:1), preferably (4:1) to (2:1).

[0036] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 The XRD patterns of the CoNi / C composite catalysts prepared in Examples 1-3 of the present invention are shown. CoNi / C-CP is the XRD pattern of the CoNi / C composite catalyst prepared in Example 1; CoNi / C-Sol-GEl is the XRD pattern of the CoNi / C composite catalyst prepared in Example 2; CoNi / C-HT is the XRD pattern of the CoNi / C composite catalyst prepared in Example 3;

[0039] Figure 2 The SEM image of the CoNi / C composite catalyst prepared in Example 1 of the present invention is shown;

[0040] Figure 3 The SEM image of the CoNi / C composite catalyst prepared in Example 2 of the present invention is shown;

[0041] Figure 4 The SEM image of the CoNi / C composite catalyst prepared in Example 3 of the present invention is shown. DETAILED DESCRIPTION

[0042] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0043] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.

[0046] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0047] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.

[0048] According to an embodiment of the present invention, the present invention provides an application of a CoNi / C composite material in a dehydrochlorination reaction of fluorochloroalkanes, and a preparation method of the CoNi / C composite material comprises contacting a cobalt source, a nickel source and a carbon source to obtain the CoNi / C composite material.

[0049] Specifically, the preparation method of the CoNi / C composite material is not particularly limited, and includes but is not limited to a sol-gel method, a hydrothermal method, and a co-precipitation reduction method.

[0050] According to a specific embodiment of the present invention, the types of the cobalt source, nickel source and carbon source are not particularly limited, and those skilled in the art can choose according to actual needs. As some specific examples, the cobalt source includes but is not limited to Co(C2H3O2)2, Co(NO3)2, CoCl2; the nickel source includes but is not limited to Ni(C2H3O2)2, Ni(NO3)2, NiCl2; the carbon source can be selected from trimesic acid, citric acid, polyvinylpyrrolidone, glycine, urea, etc.

[0051] According to a specific embodiment of the present invention, the cobalt source and the nickel source react at a molar ratio of cobalt element to nickel element of 1:1.

[0052] According to a specific embodiment of the present invention, the molar ratio of the cobalt source, the nickel source and the carbon source is 1:1:(1-4), for example, the molar ratio of the cobalt source, the nickel source and the carbon source can be 1:1:1, 1:1:2, 1:1:3, 1:1:4, preferably 1:1:(2-3).

[0053] According to a specific embodiment of the present invention, the preparation method of the CoNi / C composite material includes:

[0054] Dissolving a cobalt source, a nickel source, a carbon source and an alkaline compound in a first solvent to obtain a first precursor of a CoNi / C composite material;

[0055] The first precursor of the CoNi / C composite material is first calcined to obtain the CoNi / C composite material. That is, the CoNi / C composite material is prepared by a coprecipitation reduction method. In the preparation method, the cobalt source is preferably CoCl2, the nickel source is NiCl2, and the carbon source is an organic carbon source, which is dissolved in a solvent with an alkaline compound to undergo a coprecipitation reaction to obtain a first precursor of the CoNi / C composite material. The precursor is calcined to obtain the CoNi / C composite material by high-temperature self-reduction and pyrolysis.

[0056] Specifically, the cobalt source includes but is not limited to CoCl2, the nickel source includes but is not limited to NiCl2, and the carbon source includes but is not limited to trimesic acid.

[0057] Specifically, the type of the alkaline compound is not particularly limited as long as the precipitation of Ni and Co elements can be achieved. Those skilled in the art can select the alkaline compound according to actual needs. Some specific examples include but are not limited to hydroxides, such as NaOH.

[0058] Specifically, the type of the first solvent is not particularly limited, and those skilled in the art may select the first solvent according to actual needs. Some specific examples include but are not limited to N,N-dimethylformamide.

[0059] Specifically, the temperature and time of the first calcination are not particularly limited, as long as the reduction and pyrolysis of the CoNi / C composite material precursor are achieved. As some specific examples, the temperature of the first calcination is 400-800° C., such as 400° C., 500° C., 600° C., 700° C., 800° C., etc., preferably 500-600° C. The time of the first calcination is 1-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc., preferably 2-4 hours.

[0060] Specifically, the first calcination is performed in an inert atmosphere, including but not limited to nitrogen.

[0061] According to a specific embodiment of the present invention, the preparation method of the CoNi / C composite material includes:

[0062] The cobalt source, the nickel source and the carbon source are mixed to obtain a second precursor of the CoNi / C composite material;

[0063] The second precursor of the CoNi / C composite material is subjected to a second calcination to obtain the CoNi / C composite material. That is, the CoNi / C composite material is prepared by a sol-gel method. The preparation method preferably comprises a cobalt source of Co(NO3)2, a nickel source of Ni(NO3)2, and a carbon source of an organic carbon source (such as citric acid), wherein the three are mixed to form a sol-gel, and dried to obtain the second precursor of the CoNi / C composite material. The precursor is calcined to obtain the CoNi / C composite material.

[0064] Specifically, the cobalt source includes but is not limited to Co(NO3)2, the nickel source includes but is not limited to Ni(NO3)2, and the carbon source includes but is not limited to citric acid.

[0065] Specifically, the mixing treatment includes but is not limited to magnetic stirring. The stirring time is not particularly limited to achieve a stable sol-gel. As some specific examples, it can be 4 to 10 hours, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., preferably 6 to 8h.

[0066] Specifically, the temperature and time of the second calcination are not particularly limited. As some specific examples, the temperature of the second calcination is 300-600°C, such as 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, etc. The time of the second calcination is 3-6h, such as 3h, 4h, 5h, 6h, etc.

[0067] Specifically, the second calcination is carried out in a H2 / N2 atmosphere, wherein the volume ratio of H2 to N2 can be (1:1) to (1:5), for example, 1:1, 1:2, 1:3, 1:4, 1:5, etc., preferably (1:2) to (1:4).

[0068] According to a specific embodiment of the present invention, the preparation method of the CoNi / C composite material includes:

[0069] The cobalt source, the nickel source and the carbon source are dissolved in a second solvent and subjected to hydrothermal treatment to obtain the CoNi / C composite material. That is, the CoNi / C composite material is prepared by a hydrothermal method. The preferred preparation method is that the cobalt source is Co(C2H3O2)2 and the nickel source is Ni(C2H3O2)2. The cobalt source, the nickel source and the carbon source are mixed, dissolved in a solvent and subjected to hydrothermal treatment to obtain the CoNi / C composite material.

[0070] Specifically, the cobalt source includes but is not limited to Co(C2H3O2)2, the nickel source includes but is not limited to Ni(C2H3O2)2, and the carbon source includes but is not limited to polyvinyl pyrrolidone (PVP).

[0071] Specifically, the type of the second solvent is not particularly limited, and those skilled in the art may select the second solvent according to actual needs. As some specific examples, the second solvent includes but is not limited to hydrazine hydrate.

[0072] Specifically, the temperature and time of the hydrothermal treatment are not particularly limited. As some specific examples, the temperature of the hydrothermal treatment is 90 to 160° C., such as 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., etc. The time of the hydrothermal treatment is 8 to 24 hours, such as 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, etc., preferably 14 to 20 hours.

[0073] According to a specific embodiment of the present invention, the fluorochloroalkanes include but are not limited to 2-chloro-1,1,1,2-tetrafluoropropane, that is, the CoNi / C composite material is used for dehydrochlorination of 2-chloro-1,1,1,2-tetrafluoropropane to prepare 2,3,3,3-tetrafluoropropene.

[0074] According to a specific embodiment of the present invention, the temperature and pressure of the fluorochloroalkane dehydrochlorination reaction are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the temperature of the fluorochloroalkane dehydrochlorination reaction is 400-600° C., such as 400° C., 450° C., 500° C., 550° C., 600° C., etc., preferably 450-550° C. The pressure of the fluorochloroalkane dehydrochlorination reaction is 0.1013-1 MPa, such as 0.1013 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1 MPa, etc., preferably 0.5-0.7 MPa.

[0075] According to a specific embodiment of the present invention, the fluorochloroalkane dehydrochlorination reaction includes reacting 2-chloro-1,1,1,2-tetrafluoropropane with hydrogen to obtain 2,3,3,3-tetrafluoropropene. H2 can be used as a diluent to help the entire reaction process to be heated evenly, inhibit carbon deposition of the catalyst (CoNi / C composite material) and maintain the zero valence state of each component alloy metal in CoNi, thereby ensuring that the catalyst does not undergo changes in phase structure during the reaction and stabilizing the active center of the catalyst.

[0076] Specifically, the molar ratio of the hydrogen to 2-chloro-1,1,1,2-tetrafluoropropane is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the molar ratio of the hydrogen to 2-chloro-1,1,1,2-tetrafluoropropane can be (6:1) to (1:1), such as 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, etc., preferably (4:1) to (2:1).

[0077] Specifically, the space velocity of the fluorochloroalkane dehydrochlorination reaction is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the space velocity of the fluorochloroalkane dehydrochlorination reaction can be 600h -1 The "space velocity" should be understood as the ratio of the total volume (or total mass) of the mixed gas of 2-chloro-1,1,1,2-tetrafluoropropane and hydrogen passing through the catalyst bed to the total volume (or weight) of the catalyst per unit time.

[0078] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0079] Example 1

[0080] Dissolve 0.06 mol of trimesic acid in a round-bottom flask containing 80 mL of N,N-dimethylformamide and 1 M NaOH, and slowly add 0.03 mol of NiCl2 and 0.03 mol of CoCl2 at the same time, and heat in an oil bath at 140°C for 8 hours. After the reaction, wash with N,N-dimethylformamide and anhydrous ethanol, and dry at 80°C for 12 hours to obtain a CoNi / C composite catalyst precursor. Place the composite catalyst precursor in a tubular furnace and calcine at 500°C under a N2 atmosphere for 4 hours; obtain a CoNi / C composite catalyst by high-temperature self-reduction and pyrolysis, press into tablets after cooling, and sieve with a standard sieve of 20 to 40 meshes. The X-ray diffraction pattern (XRD pattern) of the catalyst is shown in Figure 1 , it can be seen that the catalyst includes CoNi alloy. The scanning electron microscope (SEM) test results of the catalyst are shown in Figure 2 , it can be seen that the catalyst is nanoscale.

[0081] The CoNi / C composite catalyst prepared above was used to synthesize HFO-1234yf from HCFC-244bb by removing HCl. The reaction formula is as follows:

[0082]

[0083] The reaction conditions were as follows: 2 mL of catalyst was loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb were introduced, the molar ratio of hydrogen to HCFC-244bb was 4:1, and the total space velocity of the mixed gas was 600 h -1, reaction temperature is 450℃, pressure is 0.5Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of reactant HCFC-244bb is 47.45%, the selectivity of HFO-1234yf is 94.12%, and the conversion rate of reactant is 46.1%, and the selectivity of HFO-1234yf is 94.8% after 30h of reaction.

[0084] Example 2

[0085] Add 1 mol of citric acid to 0.03 mol Co(NO3)2 and 0.03 mol Ni(NO3)2 solution, and form a sol-gel after magnetic stirring at 60°C for 6 hours. Transfer it to a forced air drying oven and further dry and dehydrate it to form a catalyst precursor. Put the precursor composite catalyst into a tubular furnace, and pass a certain volume ratio of H2 / N2 mixed gas into the tubular furnace, and the volume ratio of H2 and N2 is 1:2. Roast at 500°C for 4 hours, cool naturally to room temperature after the roasting, press into tablets and sieve with a standard sieve of 20-40 mesh. The X-ray diffraction pattern (XRD pattern) of the catalyst is shown in Figure 1 , it can be seen that the catalyst includes CoNi alloy. The scanning electron microscope (SEM) test results of the catalyst are shown in Figure 3 , it can be seen that the catalyst is nanoscale.

[0086] The CoNi / C composite catalyst prepared above was used for synthesizing HFO-1234yf by removing HCl from HCFC-244bb.

[0087] The reaction conditions are as follows: 2 mL of catalyst was loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb were introduced, the molar ratio of H2 to HCFC-244bb was 2:1, and the total space velocity of the mixed gas was 600 h -1 , reaction temperature is 550℃, pressure is 0.7Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of reactant HCFC-244bb is 45.45%, and the selectivity of HFO-1234yf is 96.78%. Samples are taken for analysis after 30h of reaction, and the conversion rate of reactant is 44.13%, and the selectivity of HFO-1234yf is 96.18%.

[0088] Example 3

[0089] 0.03 mol Co(C2H3O2)2, 0.03 mol Ni(C2H3O2)2 and 3 g polyvinylpyrrolidone (PVP) were dissolved in 100 mL ethylene glycol to form a mixed solution. Then 20 mL hydrazine hydrate (N2H4·H2O, 80 wt%) was added dropwise to the mixed solution and transferred to a 200 mL polytetrafluoroethylene-lined autoclave and hydroheated at 150°C for 14 h. After cooling naturally to room temperature, the target catalyst was obtained after centrifugal washing. The X-ray diffraction pattern (XRD pattern) of the catalyst is shown in Figure 1 , it can be seen that the catalyst includes CoNi alloy. The scanning electron microscope (SEM) test results of the catalyst are shown in Figure 4 , it can be seen that the catalyst is nanoscale.

[0090] The CoNi / C composite catalyst prepared above was used for synthesizing HFO-1234yf by removing HCl from HCFC-244bb.

[0091] The reaction conditions are as follows: 2 mL of catalyst was loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb were introduced, the molar ratio of H2 to HCFC-244bb was 3:1, and the total space velocity of the mixed gas was 600 h -1 , reaction temperature is 500℃, pressure is 0.6Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of reactant 2HCFC-244bb is 43.37%, and the selectivity of HFO-1234yf is 95.13%. Samples are taken for analysis after 30h of reaction, and the conversion rate of reactant is 42.73%, and the selectivity of HFO-1234yf is 96.23%.

[0092] Comparative Example 1

[0093] Dissolve 0.06 mol of trimesic acid in a round-bottom flask containing 80 mL of N,N-dimethylformamide and 1 M NaOH, and slowly add 0.03 mol NiCl2 and 0.03 mol CoCl2 at the same time, and heat in an oil bath at 140°C for 8 hours. After the reaction, wash with N,N-dimethylformamide and anhydrous ethanol, dry at 80°C for 12 hours to obtain a CoNi / C composite catalyst precursor. Put the composite catalyst precursor into a tubular furnace and calcine it at 500°C in a N2 atmosphere for 4 hours; high-temperature self-reduction and pyrolysis to obtain a CoNi / C composite catalyst, which is pressed into tablets after cooling and sieved with a 20-40 mesh standard sieve.

[0094] The CoNi / C composite catalyst prepared above was used for synthesizing HFO-1234yf by removing HCl from HCFC-244bb.

[0095] The reaction conditions are as follows: 2 mL of catalyst was loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb were introduced, the molar ratio of H2 to HCFC-244bb was 10:1, and the total space velocity of the mixed gas was 600 h -1 , reaction temperature is 450℃, pressure is 0.5Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of reactant HCFC-244bb is 15.12%, and the selectivity of HFO-1234yf is 77.48%. Samples are taken for analysis after 30h of reaction, and the conversion rate of reactant is 13.78%, and the selectivity of HFO-1234yf is 82.9%.

[0096] Comparative Example 2

[0097] Add 1 mol of citric acid to 0.03 mol Co(NO3)2 and 0.03 mol Ni(NO3)2 solution, and form a sol-gel after magnetic stirring at 60°C for 6 hours. Transfer it to a forced air drying oven for further drying and dehydration to form a catalyst precursor. Put the precursor composite catalyst into a tubular furnace, and introduce a certain volume ratio of H2 / N2 mixed gas into the tubular furnace, with a volume ratio of H2 to N2 of 1:2. Roast at 500°C for 4 hours, and naturally cool to room temperature after the roasting is completed, press into tablets and sieve with a standard sieve of 20-40 mesh.

[0098] The CoNi / C composite catalyst prepared above was used for synthesizing HFO-1234yf by removing HCl from 2HCFC-244bb.

[0099] The reaction conditions are as follows: 2 mL of catalyst was loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb were introduced, the molar ratio of H2 to HCFC-244bb was 2:1, and the total space velocity of the mixed gas was 600 h -1 , reaction temperature is 350℃, pressure is 0.7Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of the reactant HCFC-244bb is 11.45%, and the selectivity of HFO-1234yf is as high as 95.8%. Samples are taken for analysis after 30h of reaction, and the conversion rate of the reactant is 9.83%, and the selectivity of HFO-1234yf is 97.2%.

[0100] Comparative Example 3

[0101] Dissolve 0.06 mol of trimesic acid in a round-bottom flask containing 80 mL of N,N-dimethylformamide and 1M NaOH, and slowly add 0.06 mol of CoCl2. Heat in an oil bath at 140°C for 8 hours. After the reaction, wash with N,N-dimethylformamide and anhydrous ethanol, dry at 80°C for 12 hours to obtain a Co / C composite catalyst precursor. Put the composite catalyst precursor into a tubular furnace and calcine it at 500°C in a N2 atmosphere for 4 hours; high-temperature self-reduction and pyrolysis to obtain a Co / C composite catalyst, which is pressed into tablets after cooling and sieved with a 20-40 mesh standard sieve.

[0102] The Co / C composite catalyst prepared above was used for synthesizing HFO-1234yf by removing HCl from HCFC-244bb.

[0103] The reaction conditions are as follows: 2 mL of catalyst is loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb are introduced, the molar ratio of H2 to HCFC-244bb is 4:1, and the total space velocity of the mixed gas is 600 h -1 , reaction temperature is 450℃, pressure is 0.5Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of the reactant HCFC-244bb is 15.28%, and the selectivity of HFO-1234yf is 94.12%. Samples are taken for analysis after 30h of reaction, and the conversion rate of the reactant is 12.93%, and the selectivity of HFO-1234yf is 95.46%.

[0104] Comparative Example 4

[0105] Dissolve 0.06 mol of trimesic acid in a round-bottom flask containing 80 mL of N,N-dimethylformamide and 1M NaOH, and slowly add 0.06 mol of NiCl2. Heat in an oil bath at 140°C for 8 hours. After the reaction, wash with N,N-dimethylformamide and anhydrous ethanol, dry at 80°C for 12 hours to obtain a Ni / C composite catalyst precursor. Put the composite catalyst precursor into a tubular furnace and calcine it at 500°C in a N2 atmosphere for 4 hours; obtain a Ni / C composite catalyst by high-temperature self-reduction and pyrolysis, press into tablets after cooling, and sieve with a 20-40 mesh standard sieve.

[0106] The Ni / C composite catalyst prepared above is used for synthesizing HFO-1234yf by removing HCl from HCFC-244bb.

[0107] The reaction conditions are as follows: 2 mL of catalyst is loaded into a nickel tube in a fixed bed reactor, H2 and HCFC-244bb are introduced, the molar ratio of H2 to HCFC-244bb is 4:1, and the total space velocity of the mixed gas is 600 h -1, reaction temperature is 450℃, pressure is 0.5Mpa. Samples are taken for analysis after 3h of reaction. The results are: the conversion rate of the reactant HCFC-244bb is 16.45%, and the selectivity of HFO-1234yf is 91.12%. Samples are taken for analysis after 30h of reaction, and the conversion rate of the reactant is 18.69%, and the selectivity of HFO-1234yf is 90.71%.

[0108] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0109] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. Application of a CoNi / C composite material in dehydrochlorination reaction of fluorochloroalkanes, characterized in that: The preparation method of the CoNi / C composite material comprises contacting a cobalt source, a nickel source and a carbon source to obtain the CoNi / C composite material.

2. The use according to claim 1, characterized in that: The cobalt source includes at least one of Co(C2H3O2)2, Co(NO3)2, and CoCl2.

3. The use according to claim 1, characterized in that: The nickel source includes at least one of Ni(C2H3O2)2, Ni(NO3)2, and NiCl2.

4. The use according to claim 1, characterized in that: The carbon source includes at least one of trimesic acid, citric acid, polyvinyl pyrrolidone, glycine and urea.

5. The use according to claim 1, characterized in that: The preparation method of the CoNi / C composite material comprises: Dissolving a cobalt source, a nickel source, a carbon source and an alkaline compound in a first solvent to obtain a first precursor of a CoNi / C composite material; calcining the first precursor of the CoNi / C composite material to obtain the CoNi / C composite material; Optionally, the cobalt source comprises CoCl2, the nickel source comprises NiCl2, and the carbon source comprises trimesic acid; Optionally, the alkaline compound comprises NaOH; Optionally, the first solvent comprises N,N-dimethylformamide; Optionally, the first calcination temperature is 400-800°C, preferably 500-600°C; Optionally, the first calcination time is 1 to 6 hours, preferably 2 to 4 hours; Optionally, the first calcination atmosphere is an inert atmosphere, preferably nitrogen.

6. The use according to claim 1, characterized in that: The preparation method of the CoNi / C composite material comprises: The cobalt source, the nickel source and the carbon source are mixed to obtain a second precursor of the CoNi / C composite material; calcining the second precursor of the CoNi / C composite material for the second time to obtain the CoNi / C composite material; Optionally, the cobalt source comprises Co(NO3)2, the nickel source comprises Ni(NO3)2, and the carbon source comprises citric acid; Optionally, the second calcination temperature is 300-600°C; Optionally, the second roasting time is 3 to 6 hours; Optionally, the second calcination atmosphere is H2 / N2, and the volume ratio of H2 to N2 is (1:1) to (1:5), preferably (1:2) to (1:4).

7. The use according to claim 1, characterized in that: The preparation method of the CoNi / C composite material comprises: Dissolving a cobalt source, a nickel source, and a carbon source in a second solvent, and performing a hydrothermal treatment to obtain the CoNi / C composite material; Optionally, the cobalt source comprises Co(C2H3O2)2, the nickel source comprises Ni(C2H3O2)2, and the carbon source is polyvinylpyrrolidone; Optionally, the second solvent comprises hydrazine hydrate; Optionally, the temperature of the hydrothermal treatment is 90 to 160°C; Optionally, the hydrothermal treatment time is 8 to 24 hours, preferably 14 to 20 hours.

8. The use according to claim 1, characterized in that: The fluorochloroalkanes include 2-chloro-1,1,1,2-tetrafluoropropane.

9. The use according to claim 8, characterized in that: The temperature of the fluorochloroalkane dehydrochlorination reaction is 400-600°C, preferably 450-550°C; Optionally, the pressure of the fluorochloroalkane dehydrochlorination reaction is 0.1013 to 1 MPa, preferably 0.5 to 0.7 MPa.

10. The use according to claim 8, characterized in that: The fluorochloroalkane dehydrochlorination reaction comprises reacting 2-chloro-1,1,1,2-tetrafluoropropane with hydrogen to obtain 2,3,3,3-tetrafluoropropene; Optionally, the molar ratio of hydrogen to 2-chloro-1,1,1,2-tetrafluoropropane is (6:1) to (1:1), preferably (4:1) to (2:1).